1999
DOI: 10.1038/sj.onc.1203058
|View full text |Cite
|
Sign up to set email alerts
|

p53 accumulation in apoptotic macrophages is an energy demanding process that precedes cytochrome c release in response to nitric oxide

Abstract: Apoptosis in response to stress signals activates e ector caspases known to be regulated by the release of cytochrome c (Cyt c) from mitochondria and the subsequent ATP-dependent activation of the death regulator apoptotic protease-activating factor 1 (Apaf-1). Experiments were carried out to determine whether the release of Cyt c is evoked by NO . in RAW 264.7 macrophages and to position signaling components relative to mitochondria. S-nitrosoglutathione and spermine-NO caused a fast p53 accumulation, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 46 publications
3
31
0
Order By: Relevance
“…At this time, we can only speculate how SNP promotes TRAILinduced apoptosis. Several studies have shown that NO stimulates apoptosis through activation of caspases (Tamatani et al, 1998), cytochrome c release (Ushmorov et al, 1999), changes in the expression of pro-and anti-apoptotic Bcl-2 family members (Tamatani et al, 1998; Brockhaus and Brune, 1999), and upregulation of the tumor suppressor p53 (Brockhaus and Brune, 1999). Mitochondrial damage (lipid degradation, lipid peroxidation, and cytochrome c release) induced by NO plays a crucial role in the subsequent activation of caspase and apoptosis (Ushmorov et al, 1999;Ghafourifar et al, 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…At this time, we can only speculate how SNP promotes TRAILinduced apoptosis. Several studies have shown that NO stimulates apoptosis through activation of caspases (Tamatani et al, 1998), cytochrome c release (Ushmorov et al, 1999), changes in the expression of pro-and anti-apoptotic Bcl-2 family members (Tamatani et al, 1998; Brockhaus and Brune, 1999), and upregulation of the tumor suppressor p53 (Brockhaus and Brune, 1999). Mitochondrial damage (lipid degradation, lipid peroxidation, and cytochrome c release) induced by NO plays a crucial role in the subsequent activation of caspase and apoptosis (Ushmorov et al, 1999;Ghafourifar et al, 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ATP-depleted cells showed a shift from apoptosis towards necrosis upon NO addition, together with attenuated p53 accumulation and caspase activation. 21 We suggest that NO-mediated apoptosis in macrophages is entirely controlled by the mitochondrial pathway with the implication that p53 accumulation is upstream of cytochrome c release. This assumption is supported by the observation that thymocytes from p53 knockout-mice are protected against irradiation-induced apoptosis together with suppressed mitochondrial transmembrane depolarization.…”
Section: No-evoked Apoptosis: Initial Observationsmentioning
confidence: 99%
“…41,42 Demonstrating that a caspase-3-like or a pan-caspase inhibitor left cytochrome c and p53 accumulation unaltered implied that a caspase activity is not required for both events. 21 In close analogy to the macrophage system the ability of NO to initiate cell death with the occurrence of apoptotic parameters was identified in vascular smooth muscle cells of murine and human origin. 43,44 In these cells apoptosis was characterized by p53 accumulation, decreased Bcl-2 expression, and caspase-3 activation with the further notion that inhibition of caspase-3 significantly prevented apoptosis.…”
Section: No-evoked Apoptosis: Initial Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the findings are remarkably similar to the neutrophil infiltration observed in the thymus after irradiation (Uchimura et al, 2000) and in vitro studies have shown that phagocytosis of apoptotic cells results in the production of both pro-and anti-inflammatory cytokines (Giles et al, 2000;Gregory, 2000). Additionally, nitric oxide can be either pro-or antiapoptotic, can either downregulate or upregulate p53 activity (Brune et al, 1996;Brockhaus and Brune, 1999) and may be pro-or anti-inflammatory (Nathan and Shiloh, 2000) depending on the context. Thus, it is possible that nonspecific inflammatory-type responses to radiation-induced stress and injury may contribute to the wide variety of bystander-mediated effects and to genomic instability.…”
Section: Inflammatory-type Processes As Sources Of Bystander Signals mentioning
confidence: 99%